Anti-convulsant action and amelioration of oxidative stress by Glycyrrhiza glabra root extract in pentylenetetrazole- induced seizure in albino rats - Chowdhury, Bimalendu (Medknow Publications & Media Pvt Ltd, 2013)
OBJECTIVES: The aim of the present study was to evaluate the anti-convulsant potential of aqueous and ethanol e xtract of Glycyrrhiza glabra (AEGG and EEGG) and its action on markers of oxidant stress in albino rats. MATERIALS AND METHODS: The aqueous and ethanol extract of Glycyrrhiza glabra was tested at three doses viz. 100, 200, and 400 mg/kg i.p. for its anti-convulsant activity using pentylenetetrazole (PTZ)-induced seizure in rat. The effect of EEGG (400 mg/kg, i.p.) on oxidative stress markers like malondialdehyde (MDA), superoxide dismutase (SOD), and catalase (CAT) of rat brain tissue homogenate was tested. RESULTS: The onset of seizure was delayed (P < 0.01) by all the three doses of EEGG, but the duration of convulsion was reduced (P < 0.01) only in higher dose level (200 and 400 mg/ kg), whereas AEGG up to 400 mg/kg did not alter any of the parameters significantly. Biochemical analysis of rat brain tissue revealed that MDA was increased (P < 0.01), whereas SOD and CAT were decreased (P < 0.01) in PTZ-induced seizure rat, whereas pre-treatment with EEGG (400 mg/kg) decreased (P < 0.01) the MDA and increased (P < 0.01) both SOD and CAT, indicating attenuation of lipid peroxidation due to increase in antioxidant enzymes. CONCLUSION: The results demonstrated that EEGG poses anti-convulsant potential and ameliorates ROS induced neuronal damage in PTZ-induced seizure.